Las plumas en los rituales inkas de Tambo Viejo - Valdez, Lidio M.; Bettcher, Katrina J.; Serván, R. Fernando; Zárate, Florentino (Pontificia Universidad Católica del Perú, 2025)
The Inka state was well aware that the natural world we live in coexists with an invisible, supernatural world inhabited by divine beings who—from their standpoint—influenced human life. In order to establish and maintain good relations with these beings, the Inkas found it convenient to organise ritual ceremonies and to make various offerings. The gods corresponded to this show of goodwill by sending rains that made good harvests possible. The goods offered as presents were the best available and these included multicoloured bird feathers. This paper presents the archaeological excavations undertaken at the Inka provincial centre of Tambo Viejo, where tropical bird feathers have been found amidst several of the offerings placed inside storehouses. Here we discuss the ritual use of these items throughout the Inka period, and the special significance of their discovery amongst these goods items outside the capital city of Tawantinsuyu.

El Estado inka reconoció que el mundo natural en el que vivimos coexiste con un mundo invisible y sobrenatural habitado por seres divinos que, desde su perspectiva, tenían influencia en la vida humana. Para establecer y mantener una buena relación con ellos, los inkas vieron conveniente organizar ceremonias rituales y entregar una diversidad de ofrendas. A esta acción de buena voluntad, los dioses reciprocaron enviando lluvias que permitieron buenas cosechas. Los productos ofrecidos como regalos eran los mejores que existían, entre los cuales se encontraban las plumas de aves multicolores. Este artículo aborda las investigaciones arqueológicas realizadas en el centro provincial inka de Tambo Viejo, donde, entre varias de las ofrendas depositadas en almacenes, se hallaron plumas de aves tropicales. Aquí discutimos el uso ritual de estos productos durante la época de los inkas y el significado especial de encontrar estos objetos fuera de la capital del Tawantinsuyu.
Feathers in inka rituals at Tambo Viejo
Keywords: Inka state; Ritual; Tambo Viejo; Offerings; Camelids; Feathers; Estado inka; Ritual; Tambo Viejo; Ofrendas; Camélidos; Plumas; https://purl.org/pe-repo/ocde/ford#6.01.02